Oral Complications Due to Medication in Stevens-Johnson Syndrome Patient with Systemic Involvement - Rahmi Harmiyati; Fika Faradillah Drakel; Riani Setiadhi (Denta Journal Kedokteran Gigi, 2024)
Background: Stevens-Johnson Syndrome (SJS) is a drug-induced hypersensitivity reaction involving mucocutaneous with various trigger factors including drugs and herpes simplex virus. Objective: This case report aimed to discuss oral complications due to medication in SJS patients with systemic disease involvement. Case: A 51-year-old man was referred to the Department of Oral Medicine, Faculty of Dentistry, Padjadjaran University, at Hasan Sadikin Hospital from the dermatology and venereology department complaining of pain in the oral cavity, especially when eating and drinking two months before, with a history of phenytoin, salbutamol and theophylline therapy. Extraoral examination showed erosive lesions and tended to bleed serosanguinolenta crusts on the lips. Intraoral there were erosive lesions and white plaque on the tongue, buccal mucosa, labial mucosa, and palate, as well as dental caries and calculus. Blood examination showed low hemoglobin, hematocrit, erythrocytes, lymphocytes, monocytes, SGOT, and sodium levels, while HbA1c, random, fasting, and 2 HPP glucose levels were high. Reactive Anti-HSV-1 IgG and rheumatoid factor. KOH examination showed positive spores, hyphae, pseudohypha, and budding cells. The diagnosis was SJS-associated oral lesions with HSV-1 virus infection, oral candidiasis accompanied with diabetes mellitus. For diabetes mellitus treatment, he was referred to the internal medicine department. Case Management: The therapy was 0.9% NaCl for lip compress, acyclovir tablet, nystatin oral suspension, chlorhexidine digluconate 0,12% mouthwash, folic acid, and vitamin B12. Oral lesions were improved significantly after diabetes mellitus was treated. Conclusion: The SJS patient was susceptible to complications in the oral cavity, especially fungal and viral infections due to the received medication.